2020
DOI: 10.1136/ijgc-2019-001109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PD-L1 and T-cell inflamed gene expression profile on survival in advanced ovarian cancer

Abstract: ObjectiveProgrammed death ligand 1 (PD-L1) expression affects tumor evasion of immune surveillance. The prognostic value and relationship of PD-L1 expression to T-cell–inflamed immune signatures in ovarian cancer are unclear. The purpose of this study is to evaluate the impact of PD-L1 on overall survival and its correlation with an immune-mediated gene expression profile in patients with advanced ovarian cancer.Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
5
2
1
Order By: Relevance
“…The expression was reported by the combined positive score (CPS) defined as the number of PD-L1 staining cells (viable tumor cells, and lymphocytes and macrophages within tumor nests or next to it) divided by viable tumor cells x 100. PD-L1 expression was defined as CPS ≥1 [20,21]. PD-L1 expression was scored by two independent observers (MR and CT) and discussed whenever there was discordance.…”
Section: Immunohistochemical Evaluation Of B2m and Pd-l1mentioning
confidence: 99%
“…The expression was reported by the combined positive score (CPS) defined as the number of PD-L1 staining cells (viable tumor cells, and lymphocytes and macrophages within tumor nests or next to it) divided by viable tumor cells x 100. PD-L1 expression was defined as CPS ≥1 [20,21]. PD-L1 expression was scored by two independent observers (MR and CT) and discussed whenever there was discordance.…”
Section: Immunohistochemical Evaluation Of B2m and Pd-l1mentioning
confidence: 99%
“…PD-L1 expression was initially studied mostly in tumour cells. In particular, while previous reports showed a significant correlation of PD-L1 tumour cell expression with poor survival 28 , 97 , 99 , other groups demonstrated just the opposite, correlating PD-L1 with improved immune infiltration and prolonged survival 100 , 101 , 102 , 103 , 104 . This may be explained by a general increase in IFN-γ response in these tumours as IFN-γ on the one hand delivers an effective anti-tumour response, on the other hand it is a very potent inducer of PD-L1 expression in ovarian cancer cells 97 , 100 .…”
Section: The Pd-1/pd-l1 Immune Checkpoint In Ovarian Cancermentioning
confidence: 71%
“…Die PD-L1-Expression wurde zunächst vor allem auf den Tumorzellen untersucht. Während insbesondere frühere Berichte eine signifikante Korrelation der PD-L1-Tumorzellexpresion mit einem schlechten Überleben zeigten 28 , 97 , 99 , zeigen andere Arbeitsgruppen genau das Gegenteil, und korrelieren PD-L1 mit einer verbesserten Immuninfiltration und einem verlängerten Überleben 100 , 101 , 102 , 103 , 104 . Dies mag sich durch eine generell gesteigerte IFN-γ-Antwort in diesen Tumoren erklären, denn IFN-γ sorgt einerseits für eine effektive Anti-Tumor-Antwort im Ovarialkarzinom, andererseits ist es ein sehr potenter Induktor einer PD-L1-Expression in Ovarialkarzinomzellen 97 , 100 .…”
Section: Der Pd-1/pd-l1-immuncheckpoint Im Ovarialkarzinomunclassified
“…In analogy with earlier studies in different tumour settings [40,41], future studies aimed at optimising OC patient stratification for anti-PD-1/anti-PD-L1 treatments might benefit from measuring circulating TC-derived PD-L1 + MVs. Noteworthily, complementing PD-L1 assessment by IHC with quantification of plasma levels of PD-L1 + TC-derived MVs might also contribute to solve the still controversial issue of the prognostic significance of PD-L1 expression on TCs in OC patients-either high expression indicating poor prognosis [42,43], favourable prognosis [10,44,45], or irrelevancy [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…This immunotherapeutic approach requires that tumour cells and/or tumour-infiltrating immune cells express PD-L1. Despite the fact that ≥50% of advanced stage OCs express PD-L1 [10], data from clinical trials have shown unsatisfactory response rates [11][12][13][14][15][16]. Nevertheless, other trials have been designed and are currently ongoing (e.g., the ENGOT-ov46/AGO/DUO-O, ENGOT-OV43/KEYLYNK-001, and ATHENA phase III clinical studies).…”
Section: Introductionmentioning
confidence: 99%